Drug-Coated Balloon-Only Angioplasty Outcomes in Diabetic and Nondiabetic Patients with De Novo Small Coronary Vessels Disease. (1st December 2021) - Benjamin, Botey Katamu; Lu, Wenjie; Han, Zhanying; Pan, Liang; Wang, Xi; Qin, Xiaofei; Sun, Guoju; Wang, Xule; Shan, Yingguang; Li, Ran; Zheng, Xiaolin; Zhang, Wencai; et al.
Abstract : Background . The revascularization of small vessels using drug-eluting stents remains challenging. The use of the drug-coated balloon is an attractive therapeutic strategy in de novo lesions in small coronary vessels, particularly in the diabetic group. This study aimed to assess the outcomes of DCB-only angioplasty in small vessel disease. Methods . A total of 1198 patients with small vessel disease treated with DCB-only strategy were followed. Patients were divided into the diabetic and nondiabetic groups. Clinical and angiographical follow-up were organized at 12 months. The primary endpoints were target lesion failure and secondary major adverse cardiac events. Results . There was a significantly higher rate of target lesion failure among diabetic patients compared to nondiabetic [17 (3.9%) vs. 11 (1.4%), P = 0.006 ], taken separately, the rate of target lesion revascularization significantly differed between groups with a higher rate observed in the diabetic group [9 (2%) vs. 4 (0.5%), P = 0.014 ]. Diabetes mellitus remained an independent predictor for TLF (HR: 2.712, CI: 1.254–5.864, P = 0.011 ) and target lesion revascularization (HR: 3.698, CI: 1.112–12.298, P = 0.033 ) after adjustment. However, no significant differences were observed between groups regarding the target vessel myocardial infarction (0.6% vs. 0.1%, P = 0.110 ) and MACE [19 (4.4%) vs. 21 (2.7%), P = 0.120 ]. Conclusion . Drug-coated balloon-only treatment achieved lower incidence rates of TLF and MACE. Diabetes is an independent predictor for target lesion failure and target lesion revascularization at one year following DCB treatment in small coronary vessels. We observed no significant differences between groups regarding MACE in one year.